Duodenal Gastrointestinal Stromal Tumor: A Case Report (International Journal of Medical and Surgical Sciences, 2014)
Gastrointestinal Stromal tumors (GIST) are uncommon primary mesenchymal tumors arising from the gastrointestinal tract. The duodenum location is unusual. The authors present a case of duodenal GIST, mimicking a pancreatic tumor. Preoperatively computed tomography (CT) revealed a hypervascular mass of 10 cm in diameter, in the pancreatic head. Endoscopic examination showed erosion in duodenal mucosal with local bleeding. The patient underwent sucessfully pylorus-preserving pancreaticoduodenectomy.
Keywords: Tumor stromal gastrointestinal; Neoplasia de duodeno; Duodenopancreatectomía